It factors to (x+12)(x-12)
This is the same as (x-12)(x+12) as we can multiply two expressions in any order we want. This is like saying 7*5 is the same as 5*7
I used the difference of squares rule to factor x^2 - 144. It might help to write x^2 - 144 as x^2 - 12^2, then compare it to a^2 - b^2 = (a-b)(a+b)
We know that
When we have
Here ,
a is the leading coefficient
c is the constant term
so, we can compare it with
so, we get
so,
leading coefficient is 5
constant term is 6......................Answer
<span>m, because triangle ABC is similar to triangle EDC (by 3 congruent angles).</span>
Answer:
Step-by-step explanation:
Note that the area under a probability density curve must be 1.
The formula for the area of a triangle is A = (1/2)(base)(height).
Here the base is 25 units. Thus, A = 1 unit^2 = (1/2)(25 units)(height), or, after multiplying both sides of this equation by 2:
2 units^2 = ( 25 units)(height)
2 units^2
Then (height) = --------------------- = 0.08 unit
25 units
The height of the triangle is 0.08 unit.
Answer:
3.6
Step-by-step explanation:
9-0.2(4-7)^3
9-0.2(-3)^3
9 -0.2 (-27)
9-5.4=3.6